Students and supervisors interactions in master’s projects: Exploring face-to-face vs mediated communication - Khashab, Yousra El (Asian Journal of Contemporary Education, 2023)
This study aims at exploring communication practices between students and supervisors in thesis projects. The study conducted a comparison between face-to-face and mediated communication through the use of emails. The researcher used the autobiographical reflection to document examples of information communicated during the two interactions. Furthermore, it utilized semi-structured interviews with three students who were conducting their thesis in the Information Studies Department at Kuwait University. Then, the researcher conducted interviews with four students’ from other masters’ programs. The study used a qualitative method to analyze the results. The findings showed that students used face-to-face meetings and mediated communication to seek different types of information. The topics discussed varied between the face-to-face and mediated interaction. Face-to-face communication was perceived as more effective and productive, while mediated communication was easier and faster. Students used e-mails to set appointments with their supervisors, ask questions and get feedback on assignments. Students faced some communication barriers such as difficulty of sense-making and experiencing the “black-hole” phenomenon. The study suggested applying an electronic supervision system to facilitate students’ communication with their supervisors. This study has practical significance as it helps students and supervisors interact successfully during different thesis writing stages.